TENSILE BEHAVIOR EVALUATION OF CARBON NANOTUBE/POLYPROPYLENE COMPOSITES USING NONLINEAR FINITE ELEMENT MODELING - MOHAMMADPOUR, EHSAN (2013)
carbon nanotubes (CNTs) are potentially promising fibers for ultra-high-strength composites. Yet, there are many issues have to be clearly understood to realize the potential of CNTs in composites. In order to have a better understanding, a multiscale representative volume element (RYE) for modeling the axial tensile behavior of polymer matrix containing CNTs is proposed. The finite element model that was developed consists of CNT, interface and the matrix. An individual CNT was modeled according to the modified Morse Potential using a frame-like structure with nonlinear beam elements. The effect of van der Waals forces, crucial in multi-walled carbon nanotubes (MWCNTs), was modeled using nonlinear spring elements. Stress-strain response of the simulated CNTs under tension was in excellent agreement with other atomistic/continuum models. A cohesive zone model was defined to study load transfer from the surrounding polymer to the CNT.